Las tijeretas (Dermaptera, Forficulidae) en el control del pulgon en citricos - Cañellas, N.=700 1 Pinol, J.; Espadaler, X.
(En, Es)
ilus., 38 ref.
Keywords: FORFICULA AURICULARIA; INSECTA; CITRUS; MANDARINA; CONTROL BIOLOGICO; APHIDIDAE; ESPAÑA; PULGONES